PENGARUH PENGGUNAAN MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP MINAT BELAJAR IPA SISWA KELAS VII SMP NEGERI 3 SUNGGUMINASA KABUPATEN GOWA - Anwar, Muhammad Ikshan; Nurindah; Firdaus R (Jurnal Riset Guru Indonesia, 2023)
The purpose of this study was to determine the effect of using the blended learning, learning model on the learning interest of class VII F students at SMP Negeri 3 Sungguminasa, Gowa Regency. This type of research is quantitative with a pre-experimental method with a one-shot case study. Which uses treatment and measurement of a class with a quantitative approach. The sample in this study was students of class VII F, totaling 32 students. The instruments in this study were observations to see student learning activities, and questionnaires to see the effect of the experimental class. The data analysis technique used is descriptive analysis technique and inferential analysis. The results of this study indicate that there is an influence between students' learning interests and students who are taught using the blended learning model in class VII F of SMP Negeri 3 Sungguminasa, Gowa Regency, this can be seen from the results of hypothesis testing using the correlation test obtained that the value of Sig ≥ α is 0.528 ≥ 0.05. Thus it can be concluded that H1 is accepted and is rejected, meaning that there is an influence of the blended learning model on student learning interest.